Lifelong learning program's evaluation: a cost analysis study - Md Shariff, Noorul 'Ain; Abdul Kadir, Suhaida; Idris, Khairuddin; Basri, Ramli (Human Resource Management Academic Research Society, 2017)
This study aimed to compare cost of lifelong learning program particularly for Kluster Jahitan dan Pakaian at three community colleges from three different zone in Malaysia. This study only discusses the cost of programs run by community colleges from 2014 until 2016. The cost-effectiveness analysis methods were used to achieve the objectives of the study. The results found that community colleges spend 56% of the total cost in personnel costs, 43% on the cost of equipment and only 1% of the cost of materials. The financial analysis cost showed that there is a difference among community colleges.